The Dark Side of Fiscal Stimulus - Timo Trimborn; Holger Strulik (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
The output multiplier turns negative before a deficit spending program expires. We show the generality of this unpleasant finding for the standard real business cycle model. We then calibrate an extended model for the US and demonstrate how fiscal stimulus slows down economic recovery from recession in the medium-run. We discuss the slowdown from recovery w.r.t. alternative assumptions about the size and persistence of the initial shock (severity of the recession), the assumed power of the impact multiplier, and the scale and duration of the stimulus program. We also show that results are quantitatively very similar independent from whether a recession was caused by an efficiency wedge (input-financing frictions) or a labor wedge (labor market frictions). Capital stock and output are always below their laissez-faire level of recovery when fiscal stimulus expires.
Keywords: E60; H30; O40; 330; fiscal stimulus; government spending; output multiplier; economic recovery